Dual Currency Boards : A Proposal for Currency Stability - Oppers, S. (IMF Working Papers; Working Paper ;, 2000)
This paper shows that extending the convertibility guarantee of the traditional currency board to a second reserve currency brings about an automatic, market-driven change of the peg when the initial reserve currency appreciates beyond a specified level. The 'dual' currency board thus maintains the advantages of a hard peg, but avoids the economic difficulties associated with the link to an overvalued reserve currency. As an added benefit, the system has the potential to promote global currency stability, with the reserves of the dual currency board country acting as a buffer stock to the exchange cross-rate of the chosen reserve currencies.